2013
DOI: 10.1038/modpathol.2012.199
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell sarcoma: a rare and potentially under-recognized diagnostic entity with specific therapeutic implications

Abstract: Mast cell sarcoma is a rare, aggressive neoplasm composed of cytologically malignant mast cells presenting as a solitary mass. Previous descriptions of mast cell sarcoma have been limited to single case reports, and the pathologic features of this entity are not well known. Here, we report three new cases of mast cell sarcoma and review previously reported cases. Mast cell sarcoma has a characteristic morphology of medium-sized to large epithelioid cells, including bizarre multinucleated cells, and does not cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 20 publications
1
36
0
1
Order By: Relevance
“…Tryptase levels were available for 403 patients . Alvarez‐Twose demonstrated that serum tryptase levels > 20 ng mL −1 were correlated with extensive skin involvement, but not always associated with systemic forms .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tryptase levels were available for 403 patients . Alvarez‐Twose demonstrated that serum tryptase levels > 20 ng mL −1 were correlated with extensive skin involvement, but not always associated with systemic forms .…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in exon 17 including D816V were detected in 34% of patients . Mutations outside exon 17 were found in 18% of cases (Del419, F522C, ITD502–503, K509I, M541L, L852L) . In 48% of cases, KIT mutational status was mentioned as wild‐type .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other non codon 816 KIT mutations can be found{Ryan, 2013 #45;Kim, 2013 #42;Georgin-Lavialle, 2013 #301}…”
Section: Figurementioning
confidence: 99%